PROSPECTS OF INTENSIVE RECOVERY OF THERMAL POWER OF UKRAINE BASED ON COMBINED STEAM AND GAS POWER PLANTS - Кулик, Михайло Павлович; Мисак, Йосиф Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Thermal power of Ukraine is based on coal power blocks. Most of them were constructed in 1960-70, exceeded their service life and are in critical condition. Thermal power plants are still used to cover peak loads, they operate in partially loaded regime and are often stopped, hence, operational efficiency worsens, a lot of harmful substances is emitted into the environment making them leading polluters of air, water and soil. All technological and environmental issues of thermal power can be solved, for example, by using steam and gas cycle of electrical power generation in a combined cycle steam and gas power plant. Possible layout schemes of such plants are proposed by the authors. A characteristic feature of these plants is combustion of low-quality solid fuels, particularly coal, for gas unit operation. The article proposed various options of forming operational mixture for gas turbines – including heat transfer from boiler unit into circuit of gas turbine using heat pipes, use of two-stage combustion of finely-ground coal, as well as separation of air into nitrogen and oxygen enriched mixtures. In the latter case, the first of them circulates in the gas cycle, while oxygen enriched mixture is supplied for combustion, thus achieving a significant reduction of nitrogen oxides formation.